A facile precipitation synthesis of mesoporous 2-line ferrihydrite with good fluoride removal properties. Issue 103 (6th October 2015) - Zhu, Bai-Sheng; Jia, Yong; Jin, Zhen; Sun, Bai; Luo, Tao; Kong, Ling-Tao; Liu, Jin-Huai
Abstract : Mesoporous 2-line ferrihydrite with good fluoride removal performance was synthesized through a facile precipitation method. Abstract : Mesoporous 2-line ferrihydrite was synthesized through a facile precipitation method and was characterized by X-ray diffraction, transmission electron microscopy, and nitrogen adsorption–desorption isotherms. The surface area of the obtained mesoporous 2-line ferrihydrite was 331.0 m 2 g −1 . The fluoride adsorption performance was investigated. Batch adsorption experiments were conducted to study the influence of various factors such as contact time, initial fluoride concentration, temperature, pH value and co-existing anions on the adsorption of fluoride. The fluoride adsorption process fitted well with the Langmuir model, and the maximum adsorption capacity was 23.89 mg g −1 at pH 7.0. It is worth mentioning that this adsorbent performed well over a considerably wide pH range of 3–9. The fluoride adsorption kinetics over the adsorbent can be well described by a pseudo-second-order kinetic model. Thermodynamic parameters including the Gibbs free energy, standard enthalpy and standard entropy were calculated, and the results suggested that the adsorption of fluoride on the mesoporous 2-line ferrihydrite was thermodynamically favorable and exothermic in nature. Furthermore, Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy analyses revealed that the surface hydroxyl groups play an important part in the fluoride removal process.